Increased Drought Resistance 1 Mutation Increases Drought Tolerance of Upland Rice by Altering Physiological and Morphological Traits and Limiting ROS Levels. (9th April 2021) - Zu, Xiaofeng; Lu, Yanke; Wang, Qianqian; La, Yumei; Hong, Xinyue; Tan, Feng; Niu, Jiayu; Xia, Huihui; Wu, Yufeng; Zhou, Shaoxia; Li, Kun; Chen, Huhui; et al.
Abstract: To discover new mutants conferring enhanced tolerance to drought stress, we screened a mutagenized upland rice ( Oryza sativa ) population (cv. IAPAR9) and identified a mutant, named idr1-1 ( increased drought resistance 1-1 ), with obviously increased drought tolerance under upland field conditions. The idr1-1 mutant possessed a significantly enhanced ability to tolerate high-drought stresses. Map-based cloning revealed that the gene LOC_Os05g26890, residing in the mapping region of IDR1 locus, carried a single-base deletion in the idr1-1 mutant. IDR1 encodes the Gα subunit of the heterotrimeric G protein (also known as RGA1), and this protein was localized in nucleus and to plasma membrane or cell periphery. Further investigations indicated that the significantly increased drought tolerance in idr1-1 mutants stemmed from a range of physiological and morphological changes, including greater leaf potentials, increased proline contents, heightened leaf thickness and upregulation of antioxidant-synthesizing and drought-induced genes, under drought-stressed conditions. Especially, reactive oxygen species (ROS) production might be remarkably impaired, while ROS-scavenging ability appeared to be markedly enhanced due to significantly elevated expression of ROS-scavenging enzyme genes in idr1-1 mutants under drought-stressed conditions. In addition, idr1-1 mutants showed reduced expression of OsBRD1 . Altogether, these results suggest that mutation of IDR1 leads to alterations in multiple layers of regulations, which ultimately leads to changes in the physiological and morphological traits and limiting of ROS levels, and thereby confers obviously increased drought tolerance to the idr1-1 mutant.